Comparison of the effects of core stabilization exercises on muscle strength and balance in women and men - Akyüz, Ömer; Rümeysa Kirantay, Şevval; Günendi, Gizem (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The aim of this study was to investigate the effects of core stabilization exercises on balance and core muscle strength in healthy male and female individuals and to determine whether these effects differ by gender. The study was conducted at the Physiotherapy and Rehabilitation Laboratory of Istanbul Yeni Yüzyıl University. Thirty university students, aged between 18 and 30, voluntarily participated in the study. The participants were divided into two groups: 15 women and 15 men. The static balance of the participants was measured using the Flamingo Balance Test, and their dynamic balance was assessed using the Y-Balance Test. The core muscle strength evaluations were performed using the "Core Muscle Strength and Stability" test, which consists of 9 stages. Both groups were provided with a 6-week core stabilization exercise program, which was applied three days a week. At the end of the study, the final test results of the women and men were compared to examine the effects of core stabilization exercises, which were applied for the same duration and intensity, on balance and muscle strength. The results showed significant differences in the static and dynamic balance measurements in women (p<0.05), while no such difference was observed in men (p>0.05). No significant difference in muscle strength tests was found between women and men (p>0.05). It is important to consider gender-specific differences in the planning and implementation of core stabilization programs.